Loan and Grant Support for Students in the Context of the Diversification of Funding Sources for Higher Education - Sokolovska, Alla; Rainova, Larysa; Zatonatska, Tetiana (Ekonomika, 2019)
[full article and abstract in English]This paper considers the mechanism of direct state support for students in European countries using loans and grants: their functions, forms, schemes, and conditions for provision. The peculiarities of the state preferential educational loan in Ukraine and the reasons for its curtailment since 2011 are determined. Nowadays, it is established that the main form of state support for Ukrainian students who receive higher education in public procurement comes with academic and social scholarships, whereas students who receive higher education under a contract of preferential state lending yet after the curtailment of the program are deprived of any state support. The necessity of restoring the program of preferential state lending for students and the directions of its improvement, such as the establishment of an interest rate on a loan based on the level of inflation, the establishment of a minimum amount of annual payments on a loan as a percentage of the minimum salary, the distribution of the risk of non-repayment of a loan between the state, the borrower and his parent, are all substantiated. This is done taking into account the financial capabilities of the Ukrainian state and the high levels of hidden income. We consider the establishment of conditions needed for the development of a system of commercial educational loans, by providing for the provision of a state guarantee on it and partial state subsidy of interest rates. We consider the areas of improvement of scholarship support of students and substantiate the necessity of introducing education at least for orphans, children deprived of parental care, and disabled children.